The Role of the Village and Community Empowerment Service in the Development of Village Owned Enterprises (BUMDes) in North Labuhanbatu Regency - Luki Bakti Kusuma; Sirojuzilam; Erlina (Budapest International Research and Critics University, 2021)
This research aims to find out the role of community and village empowerment agencies in the development of BUMDes in North Labuhanbatu Regency. As an office that handles about villages, community and village empowerment agencies have the task of carrying out training, coaching, and mentoring to the development of BUMDes. The formulation of this research problem is